Design, Validation, and Reliability of an Observational Instrument for Technical and Tactical Actions in Singles Badminton - Torres-Luque, Gema (Front Psychol, 2020)
Technical and tactical actions are decisive in terms of badminton player competitive performance. The main objective of this research was to design, validate, and estimate the reliability of an observational instrument for the analysis of the tactical and technical actions in individual badminton. The process was carried out in four different steps: first, there was a review of the scientific literature and a preliminary list of variables was made; second, a qualitative and quantitative assessment was completed by 10 badminton expert judges; in the third step, the content validity was estimated using Aiken’s V coefficient; finally, intra-observer reliability and interobserver reliability were tested by two observers specialized in badminton using the Cohen’s Kappa coefficient and the intraclass correlation coefficient. Strokes were used as the unit of measure by our observational instrument; every time badminton players hit the shuttlecock, 22 variables (eight contextual variables, seven variables related to the result of the match, and seven variables related to the game) are observed. The minimum Aiken’s value was 0.58, and reliability was 0.63. In spite of these values, none of the variables had to be removed, but there were modifications in terms of drafting in some of them. The main findings confirmed the validity and the usefulness of this instrument.